Microwave absorption in the frustrated ferrimagnet Cu2OSeO3 - Kobets, M.I.; Dergachev, K.G.; Khatsko, E.N.; Rykova, A.I.; Lemmens, P.; Wulferding, D.; Berger, H. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2009)
The resonance properties of a new Cu2OSeO3 ferrimagnet have been investigated in a wide range of frequencies (17–142 GHz) at liquid helium temperature. The resonance data were used to plot the frequencyfield dependence of the ferrimagnetic spectrum described within the model of an anisotropic two-sublattice ferrimagnet. The effective magnetic anisotropy corresponding to the gap in the spin wave spectrum has been estimated (3 GHz). It is found that the spectrum has a multicomponent structure which is due to the diversity of the types of magnetization precession. As the amplitude of the high-frequency magnetic field increased, an additional absorption was observed in the external magnetic field lower than the field of the main resonance. The detected additional absorption corresponds to the nonuniform nonlinear parametric resonance, connected with nonuniformity of magnetic structure in the ferrimagnetic crystal Cu2OSeO3.